Inter- and Intramolecular Vibrational Distribution in IR Multiple Photon Excitation: CF2Cl2 Molecule. Issue 2 (1988) - Doljikov, Yu. S.; Malinovsky, A. L.; Ryabov, E. A.
Abstract : Vibrational energy distribution of IR MP-excited CF2 Cl2 is studied when pumping molecules through ν 1 and ν 8 modes. In both cases the intermolecular distribution is found to be in a state of nonequilibrium consisting of ensembles of "hot" and "cold" molecules. The structure of the "cold" ensemble is different when ν 1 and ν 8 modes are pumped. Statistical intramolecular energy distribution caused by stochastization of vibrational motion is found for "hot" molecules. The estimated value of stochastization onset energy equals Eth ≤ 7800 cm −1 .